2016
DOI: 10.1007/s10113-016-1078-0
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive capacity of institutions in Canada, Argentina, and Chile to droughts and floods

Abstract: The increasing evidence of global warming calls on all states to enhance their adaptive capacity to deal with climate change. This paper compares the adaptive capacity of two Canadian provinces, the province of Mendoza, Argentina and the administrative region of Coquimbo, Chile in relation to the vulnerability of farmers to droughts and floods by applying the adaptive capacity wheel (ACW). It concludes that Saskatchewan and Alberta, Canada are particularly weak in terms of double-and triple-loop learning and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…For example, a clause in provincial water law does require "beneficial use" and prohibits stockpiling of groundwater rights. However, in practice, groundwater rights tend to be granted 'in perpetuity' in the area, making "clawback" difficult at the time of mobilizing finance for irrigation modernization to pressurized systems like with drip and micro-spray application [66]. This rigidity contributes to a tendency to use the water that was "saved" to extend the irrigated area.…”
Section: Glacier Protection Law and Water Governance In A Strong Agrimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a clause in provincial water law does require "beneficial use" and prohibits stockpiling of groundwater rights. However, in practice, groundwater rights tend to be granted 'in perpetuity' in the area, making "clawback" difficult at the time of mobilizing finance for irrigation modernization to pressurized systems like with drip and micro-spray application [66]. This rigidity contributes to a tendency to use the water that was "saved" to extend the irrigated area.…”
Section: Glacier Protection Law and Water Governance In A Strong Agrimentioning
confidence: 99%
“…Wise et al, (2014) [22] describe a series of iterative decision cycles, where a pathway to the future may be identified that appears suitable in the current time period, and which undergoes regular reevaluation so that further changes can be undertaken as required. The Mendosa case study illustrates this need for ongoing refinements: The national law protecting the glaciers was a first step to ensure the water supply, and then subsequent measures and changes were identified related to the institutions that distribute water [66]. This recognition of accommodating the process of change also arises in the economics of adaptation, where decision-making under uncertainty includes maintaining flexibility in adaptation decisions where possible and selecting adaptation options that can be revisited and adjusted as more information becomes available.…”
Section: Facilitating Ability To Change Through Flexibility and Learningmentioning
confidence: 99%
“…It defines six main dimensions divided into 22 adaptive capacities ( Table 1). The ACW has been applied to a myriad of water related topics, including climate change [24], droughts and floods [25], sustainability of water governance systems [26,27], and policy content analysis [28] but has not yet been applied to the diversification of FRM.…”
Section: The Adaptive Capacity Wheelmentioning
confidence: 99%
“…Previous studies, dealing with adaptive capacities, encountered various challenges rooted in understanding the capacities' definitions [25,28], and weighting can lead to misinterpretations [27]. Because of the downsides encountered by scholars, for this study, the ACW is applied only as a qualitative method, not as a quantitative or measurable approach.…”
Section: The Adaptive Capacity Wheelmentioning
confidence: 99%
“…The website of the ACT Government shows the initiatives they have established to study the climate's effect in their country and to analyze the measures and strategies to be adopted. Some related specific studies are the analysis of the vulnerability of electricity infrastructures to the events of CC in China and Japan carried out [31] or the study of the adaptation capacity of institutions in Canada, Argentina and Chile to droughts and floods [32]. All of this shows the great concern of the different administrations and organizations about the risks generated by CC, the need to carry out studies to forecast the evolution of the climate and to adopt measures which reduce the consequences of the risks detected in the population, environment or infrastructure.…”
Section: Ii3 Othersmentioning
confidence: 99%